Pelaksanaan Pembelajaran Seni Budaya Menggunakan Pembelajaran Daring Di SMA Negeri 3 Padang Panjang - Parrhesia Insani; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2020)
This study aims to describe and determine the Implementation of Culture and Arts instruction using online learning at SMA Negeri 3 Padang Panjang. This research is a qualitative research using a descriptive analysis method. The instruments used were the researcher itself and was assisted by supporting instruments such as writing instruments and mobile phones. The data were collected through interviews, literature study, and documentation. This study used primary and secondary data. The data analysis was conducted by collecting the data, identifying the data, classifying the data, describing the data, and making conclusions. The results show that the implementation of online learning has not been carried out well. This is due to the fact that there are still many students who do not participate in the process of online learning. In addition, the lesson plans used by teachers are inappropriate. The teachers still use lesson plans for classrooms instruction. This is due to the fact that there is no order from the government to create online lesson plans. The media used is very limited. The teachers use smartphones, laptops and computers. Moreover, the methods used are also limited. The teachers usually used demonstration, lectures, discussions, and assignments. Meanwhile, in online learning the teachers only give assignments. Discussions carried out during online learning are still conducted. However, there are small numbers of students respond and participate in the discussion. The assignments collected are also not on time on the grounds that students have not finished working on assignments, network problems, internet data, and others.